2004
DOI: 10.1055/s-2004-817960
|View full text |Cite
|
Sign up to set email alerts
|

Conscious Sedation: Off-Label Use of Rectal S(+)-Ketamine and Midazolam for Wound Dressing Changes in Paediatric Heat Injuries

Abstract: Conscious sedation with rectally applied S(+)-ketamine and Midazolam allows safe and painless dressing changes after heat injuries in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Ketamine has been widely used during burn dressing changes, particularly in children, orally or rectally (1,13,14). Heinrich et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine has been widely used during burn dressing changes, particularly in children, orally or rectally (1,13,14). Heinrich et al.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al. (13) studied rectal S (+)‐ketamine and midazolam for wound dressing changes in pediatric burn injuries and reported that this combination allowed safe and painless dressing changes. Humphries et al.…”
Section: Discussionmentioning
confidence: 99%
“…[3910] It is widely understood that pain is exacerbated by anxiety. In burns, the commonly used benzodiazepine is midazolam.…”
Section: Introductionmentioning
confidence: 99%
“…B. Verbandswechsel bei kleinflächigen, leichten Verbrennungen, besteht die Mög-lichkeit der rektalen Gabe von S(+)-Ketamin (0,75 mg/kgKG) und Midazolam (0,4 mg/kgKG) [19]. Hierfür müssen allerdings die beschrieben Kontraindikationen respektiert und die genannten Richtlinien für die Durchführung eingehalten werden.…”
Section: Beispiele Für Analgosedierungen Bei Kindern Mit Esketamin (Kunclassified